PERTUKARAN INFORMASI SOSIAL MELALUI ROLE-PLAYER DI TWITTER DALAM MEMBENTUK HUBUNGAN INTERPERSONAL - Diaz Saraswati (2020)
The rapid development of technology causes the way of human communication also develops. One of them is through role-player games that are carried out on social media, especially Twitter. Role-player is a role play that uses the identity of others and acts as if it were them. In role-player games, players can establish relationships, even to the point of breaking virtual boundaries. The purpose of this study is to find out, how the process of exchanging social information through role-players in order to build interpersonal relationships between players. This research is based on social information processing theory and uses a qualitative method to the type of descriptive research.The results of this study describe the stages of role-players in develop interpersonal relationships between players, namely interpersonal information, impression formation and relationship development. This research also proves that through computer-based communication can also build interpersonal relationships that are woven into the real world.